ANALISIS PENGARUH CAR, NPL, LDR, DAN BOPO TERHADAP ROA DAN HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2013-2015) - Reza Prily Restika, 13.05.51.0159 (Students Journal of Economic and Management, 2017)
This research aims to analyze the effect variable Capital Adequacy Ratio (CAR), the Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), and operating costs operating income (BOPO) against the Return On Assets (ROA) and stock price (PBV). Hypothesis testing in this study using multiple regression analysis (multiple regression).The sample used in this study as many as 41 banking company listed on the Indonesian stock exchange (idx) with a purposive sampling technique, i.e. with determinant technique with samples based on criteria. These criteria are the banking company listed on the Indonesian stock exchange (idx) of the year 2013 â 2015, the banking company that does not have financial statements year 2013 â 2015 issued in succession, companies that do not have a complete financial reports during the research period, the banking company that has no positive results on variable ROA.Research results after a test of the hypothesis partially show that CAR and LDR have significant and positive influence against ROA and the stock price, the NPL and the negative influence and BOPO significantly to ROA and the stock price. From the results it can be concluded that this greater research impact than PBV ROA as seen from the Î² value and significient.